State tax systems policy making for fiscal stability - Qiao, Yuhua (Routledge, 2025)
"State governments are responsible for most of the direct domestic spending that affects the well-being of their citizens. Fiscal stability, important for state governments to serve the public, is influenced by both state tax systems and spending programs. This important new book explores how states' tax systems have changed, particularly in the aftermath of the Great Recession, why changes were made, and how these policies contributed to state fiscal stability. Author Yuhua Qiao examines tax systems including state personal income tax, corporate income tax, sales and use tax, fuel tax, health care provider tax, and sin taxes. As fiscal stability largely depends on a tax system with a broad base and diverse sources, this book pays special attention to how changes affect the tax base, as well as the challenges and opportunities states face in broadening it. Case studies within the book provide a rich discussion about the context under which a tax reform is adopted as well as its repercussions. The first book dedicated to a comprehensive examination of tax policy changes at the state level since the Great Recession, State Tax Systems: Policy Making for Fiscal Stability will help state government officials, public finance scholars, and students gain a better understanding of a given tax policy's impact on state fiscal health over the long term"--